EFEKTIVITAS MODEL LATIHAN UMPAN MENGGUNAKAN HOOP TAKRAW DAN LATIHAN UMPAN BERPASANGAN TERHADAP AKURASI MENGUMPAN ATLET SEPAK TAKRAW REMAJA DI KABUPATEN GORONTALO - Djaina, Rizki Djaina; Hartono Hadjarati; Arief Ibnu Haryanto; I Kadek Suardika; Nurkhoiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effectiveness of passing training using a takraw hoop and paired passing training on the passing accuracy of adolescent sepak takraw athletes in Gorontalo Regency. The study employed an experimental method, providing a structured training program over 16 sessions at a frequency of 6 per week. The study utilized a two-group pretest-posttest design. The sample consisted of 20 athletes, and passing accuracy was measured using a passing accuracy test. The results indicated that: (1) passing training using a takraw hoop had a significant effect on the passing accuracy of adolescent sepak takraw athletes in Gorontalo Regency; (2) paired passing training had a significant effect on the passing accuracy of adolescent sepak takraw athletes in Gorontalo Regency, and (3) passing training using a takraw hoop was more effective than paired passing training in improving the passing accuracy of adolescent sepak takraw athletes in Gorontalo Regency.